Indirect criticisms in Mr. Pecut’s corner of Jawa Pos daily newspaper - Andi Muhtar (Jurnal Linguistik Terapan, 2013)
There are three theories of meaning, namely, the mentalistic theory, the behaviorist theory, and the use theory. Criticisms, which are given to show dislikes toward another person’s or other people’s actions/utterances, contain meanings. Criticisms in Mr. Pecut’s corner, which appear in the form of responses to statements made by public figures, are bitter but, by and large, humorous. This article will analyze the criticisms in Mr. Pecut’s corner of Jawa Pos daily newspaper and relate them with theories of meaning in linguistic philosophy.